2004
DOI: 10.13031/2013.17593
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage Identification of Beef Using an Electronic Nose System

Abstract: A commercially available Cyranose-320. conducting polymer-based electronic nose system was used to analyze the volatile organic compounds emanating from fresh beef strip loins (M. Longisimmus lumborum) stored at 4°C and 10°C. Two statistical techniques, i.e., linear discriminant analysis (LDA) and quadratic discriminant analysis (QDA), were used to develop classification models from the collected sensor signals. The performances of the developed models were validated by two different methods: leave-1-out cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
0
36
0
2
Order By: Relevance
“…Several researchers have reported the use of electronic nose systems for determining the quality of meat, grains, coffee, mushrooms, beer, cheese, fish, beverages, blueberry and sugars (Balasubramanian et al, 2004;Di Natale et al, 1997;Olsson, Borjesson, Lundstedt, & Schnurer, 2002;Schaller, Bosset, & Escher, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported the use of electronic nose systems for determining the quality of meat, grains, coffee, mushrooms, beer, cheese, fish, beverages, blueberry and sugars (Balasubramanian et al, 2004;Di Natale et al, 1997;Olsson, Borjesson, Lundstedt, & Schnurer, 2002;Schaller, Bosset, & Escher, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the performance of the 32-sensor and 10-sensor schemes were comparable (67% vs. 69%), however, the six-sensor scheme performed significantly better than its counterparts with 85% classification accuracy. Combined data 31, 5,23,6,28,26,29,9,20,18 It is interesting to note that although the six-sensor scheme trailed the other two schemes in the model cross validation, it outperformed the other two schemes considerably in the model validation. The potential reason for this performance discrepancy between the six-sensor scheme and 32-or 10-sensor schemes may lie in the fact that the four sensors (sensor 5, 6, 23, and 31) that are more sensitive to the water vapor were excluded from these six sensors.…”
Section: Svm Model Validationmentioning
confidence: 98%
“…The E-nose has been utilized in various food quality evaluation applications such as predicting apple, pear, and banana ripeness [15][16][17], identification of microbes responsible for spoiled beef [18], detection of apple defects [19][20][21], and inspection of grains for quality control [22]. The E-nose was also utilized for the Allium research in the past.…”
Section: Introductionmentioning
confidence: 99%
“…For the classification of agricultural and food materials, statistical (parametric and nonparametric) and artificial neural network classifiers have been used widely (Visen et al 2004;Majumdar and Jayas 2000b;Balasubramanian et al 2004;Dubey et al 2006). The selection of the best classifier for a particular application generally involves some degree of experimentation (Jayas et al 2000;Luo et al 1999).…”
Section: Model Development For Classificationmentioning
confidence: 99%